2017
DOI: 10.37190/epe170303
|View full text |Cite
|
Sign up to set email alerts
|

Textile dye removal using experimental wetland ponds planted with common duckweed under semi-natural conditions

Abstract: The study assesses the performance of experimental wetland pond systems vegetated by Lemna minor L. (common duckweed or lesser duckweed) for textile azo dye removal. The objectives are to assess the influence of L. minor on water quality parameters, compare the dye and chemical oxygen demand (COD) removal of four dyes (Acid Blue 113, Reactive Blue 198, Direct Orange 46 and Basic Red 46) with each other, and monitor the effect of dye accumulation as a function of the relative growth rate (RGR) of L. minor. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Plants can uptake dyes, which are the principal constituent of textile wastewater. Previously, Myriophyllum spicatum and Ceratophyllum demersum species of plants efficiently removed dyes from synthetic textile wastewater [10].…”
Section: Plant Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants can uptake dyes, which are the principal constituent of textile wastewater. Previously, Myriophyllum spicatum and Ceratophyllum demersum species of plants efficiently removed dyes from synthetic textile wastewater [10].…”
Section: Plant Selectionmentioning
confidence: 99%
“…Incompletely treated or untreated water is harmful to the environment and other living creatures [9,10]. All types of wastewater should be treated before dumping into open water bodies in order to minimize the spread of water pollution [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, no long-term study has been found in the literature on the treatment of synthetic wastewater containing azo dyes mixed with chemicals simulating effluents from textile mills using pond systems vegetated with free-floating plants under hydroponic conditions. Although shallow pond systems have been operated for the treatment of dyes mixed with synthetic wastewater for around 10 months under controlled conditions (Yaseen and Scholz 2016) and for more than 1 year under semi-natural conditions (Yaseen and Scholz 2017b), the researchers used low dye and nutrient concentrations to simulate artificial wastewater using plant fertiliser, which does not simulate the textile wastewater chemicals well. Furthermore, only a few publications focus on the long-term treatment of industrial effluents using pond systems.…”
Section: Rational and Noveltymentioning
confidence: 99%
“…According to Yaseen and Scholz (2017), the dye effluents have high levels of color, pH, suspended solids (SS), Chemical oxygen demand (COD), biological oxygen demand (BOD), metals (Sekomo et al, 2012; Sharma et al, 2007), temperature (Dos Santos et al, 2007; Shah et al, 2013), and salts. Therefore, before releasing the appropriate effluent to the receiving water body during the treatment procedures, it is crucial to check and compare these values with the standard concentrations.…”
Section: Introductionmentioning
confidence: 99%